Georgia Architectural and Historic Properties Survey of Rural (Pidcock) [221] South western section of the county, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural (Pidcock) [221] South western section of the county, Ga. December 1980. A one story rectangular plan with gabled rood and shiplap siding. Shed awning. Shuttered windows, interior chimney, brick piers. Poor condition. Was probably a country store and gas station. Date of Construction: c. 1890. This is obviously a general store used to serve the small community of Pidcock. Significant because it helped form the small settlement of Pidcock.
1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.11 MB (1,172,344 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Quitman (Ga.); Brooks County (Ga.)